Inhibition of USP7 enhances CD8+ T cell activity in liver cancer by suppressing PRDM1-mediated FGL1 upregulation - Sun Lin-lin; Zhao Li-na; Sun Jiao; Yuan Hong-feng; Wang Yu-fei; Hou Chun-yu; Lv Pan; Zhang Hui-hui; Yang Guang; Zhang Ning-ning; Zhang Xiao-dong; Lu Wei (Acta Pharmacologica Sinica, 2024)
Lymphocyte activation gene 3 (LAG3), an immune checkpoint molecule expressed on activated T cells, functions as a negative regulator of immune responses. Persistent antigen exposure in the tumor microenvironment results in sustained LAG3 expression on T cells, contributing to T cell dysfunction. Fibrinogen-like protein 1 (FGL1) has been identified as a major ligand of LAG3, and FGL1/LAG3 interaction forms a novel immune checkpoint pathway that results in tumor immune evasion. In addition, ubiquitin-specific peptidase 7 (USP7) plays a crucial role in cancer development. In this study we investigated the role of USP7 in modulation of FGL1-mediated liver cancer immune evasion. We showed that knockdown of USP7 or treatment with USP7 inhibitor P5091 suppressed liver cancer growth by promoting CD8+ T cell activity in Hepa1-6 xenograft mice and in HepG2 or Huh7 cells co-cultured with T cells, whereas USP7 overexpression produced the opposite effect. We found that USP7 upregulated FGL1 in HepG2 and Huh7 cells by deubiquitination of transcriptional factor PR domain zinc finger protein 1 (PRDM1), which transcriptionally activated FGL1, and attenuated the CD8+ T cell activity, leading to the liver cancer growth. Interestingly, USP7 could be transcriptionally stimulated by PRDM1 as well in a positive feedback loop. P5091, an inhibitor of USP7, was able to downregulate FGL1 expression, thus enhancing CD8+ T cell activity. In an immunocompetent liver cancer mouse model, the dual blockade of USP7 and LAG3 resulted in a superior antitumor activity compared with anti-LAG3 therapy alone. We conclude that USP7 diminishes CD8+ T cell activity by a USP7/PRDM1 positive feedback loop on FGL1 production in liver cancer; USP7 might be a promising target for liver cancer immunotherapy.